The Effects of Cross-Language Differences on Bilingual Production and/or Perception of Sentence-Level Intonation - Mennen, Ineke; Colantoni, Laura (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue features a collection of state-of-the art articles on the intonational patterns of different types of bilinguals (e.g., second language learners; heritage speakers; simultaneous bilinguals), with a particular focus on understudied language pairings and encompassing a wide variety of languages (e.g. Arabic, Bulgarian, Czech, German, English, French, Inuktitut, Italian, Japanese, Norwegian, and Spanish). The papers in this Special Issue address a number of questions that have so far remained unanswered: Can we determine a hierarchy of difficulty or transferability? How does prosody interact with other components of the grammar, such as morphology or syntax, in a contact situation? Which aspects are more prone to bidirectional interference? Which changes in intonation make speakers sound foreign in their second (or first) language? The papers in this Special Issue offer answers to these questions and open up multiple avenues for future research. We hope that this Special Issue will inspire future studies on intonation and bilingualism.